Clinical analysis of color change and tooth sensitivity to violet LED during bleaching treatment: A case series with split-mouth design - Gallinari, Marjorie de Oliveira [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Souza, Morganna Borges de Almeida [UNESP]; Barboza, Ana Carolina Souza [UNESP]; Esteves, Lara Maria Bueno [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Briso, André Luiz Fraga [UNESP] (Elsevier, 2019)
Background: The aim of this study was to analyze bleaching treatment performed with different products, with or without the use of Violet LED. Methods: The color and dental sensitivity of six patients were evaluated as follows: (1)at-home bleaching with 10% Carbamide Peroxide (CP); (2)in-office bleaching with 17.5% Hydrogen Peroxide (HP), and (3)treatment with a placebo gel. All patients, including patients receiving at-home bleaching, received irradiation with violet LED in the office. The right hemiarch was protect with silicone. The color was evaluated using Vita Easyshade digital spectrophotometer and the Vita scale on teeth 13-23. Visual analog scale sensitivity analysis was performed per hemiarch, while the thermal sensation threshold was performed on teeth 11, 13, 21 and 23. Results: Regarding the color change (ΔE)it can be observed that treatment 1, in which 10%CP was used, presented the highest values, followed by treatment 2, in which 17.5%HP was used. Regarding sensitivity, only patients who received 17.5%HP showed moderate sensitivity, and there was no difference between the arches. The analysis of dental thermal sensation threshold showed that there was more dental sensitization between 7 and 14 days and that the use of violet LED made the teeth more sensitive. Conclusions: It was concluded that violet LED enhanced the bleaching effect when used with 10%PC gels, and a discreet effect was seen when used either in conjunction with 17.5%PH or alone. Violet LED had no effect on pain sensation, but increased the detection threshold of thermal changes in the teeth that were irradiated.
Keywords: Dentin sensitivity; Irradiation; Tooth bleaching